Designing performance management system using balance scorecard for chemical services contractor in PT. XYZ - Syukirman, , (2014)
This paper is focus on designing company performance management in operational level for chemical services contractor at PT. XYZ that produced crude oil in Indonesia.In the oil treatment, some chemicals are used that supplied by contractor.In performing the contract services, the chemical contractor provides reports regularly to PT. XYZ, but the report was not integrated and did not shown the comprehensive contractor’s performance.Meanwhile, PT. XYZ has no integrated performance reporting system to capture overall contractor performance.There is a strong need from PT. XYZ to improve the competency of its business partners, including the chemical contractor.PT. XYZ wants to conduct contractor performance appraisal to capture lessons learned as well as to document the performance of the contractor.Through contractor performance appraisal, the company would increase it performance standard by recognizing contractor excellent performance.To improve this condition, PT. XYZ designing performance management system based on Balanced Scorecard with some objectives and critical success factors.The focus of scorecard is to define metrics that shall be tracked to validate the achievement of contractors, drive and support the right behaviors and improved performance, and in a manageable size and those which add value.The metrics focused on five objectives,i.e.: Capital Stewardship, World Class Operation, Continuous Improvement, Incident Free Operation (IFO), and People Development. Through this improvement, the performance management system developed is much better than contractor’s reporting system and enable the contractor to improve their performance.However, it was found that some weaknesses still existed and need further continuous improvement to achieve operational excellence as the objective of the company.